2010
DOI: 10.1111/j.1440-1819.2010.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between late‐life depression and life stressors: Large‐scale cross‐sectional study of a representative sample of the Japanese general population

Abstract: Aim:The purpose of the present study was to clarify the relationship between late-life depression and daily life stress in a representative sample of 10 969 Japanese subjects.Methods: Data on 10 969 adults aged Ն50 who participated in the Active Survey of Health and Welfare in 2000, were analyzed. The self-administered questionnaire included items on 21 reasons for life stressors and the magnitude of stress, as well as the Japanese version of the Center for Epidemiologic Studies Depression Scale (CES-D). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Clark et al, 2012;Finlay-Jones & Eckhardt, 1984;Hintikka et al, 2008;Jenkins et al, 2008;Meltzer et al, 2013;Patel et al, 1998. 2 Besler & Stallones, 2008Bridges & Disney, 2010;Kaji et al, 2010;Stuhldreher et al, 20073 Chan et al, 2009Chen et al, 2006;Wong et al, 2008;Wong et al, 2010. 4 Chan et al, 2009Chen et al, 2006;Hintikka et al, 2008;Wong et al, 2008;Wong et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clark et al, 2012;Finlay-Jones & Eckhardt, 1984;Hintikka et al, 2008;Jenkins et al, 2008;Meltzer et al, 2013;Patel et al, 1998. 2 Besler & Stallones, 2008Bridges & Disney, 2010;Kaji et al, 2010;Stuhldreher et al, 20073 Chan et al, 2009Chen et al, 2006;Wong et al, 2008;Wong et al, 2010. 4 Chan et al, 2009Chen et al, 2006;Hintikka et al, 2008;Wong et al, 2008;Wong et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mental health, many studies have shown a relationship with common mental disorders (Clark et al, 2012;Cooper et al, 2008;Meltzer et al, 2013;Patel et al, 1998;Pothen et al, 2003), and global mental health as measured by the General Health Questionnaire (Goldberg, 1991Brown et al, 2005Finlay-Jones & Eckhardt, 1984;Gathergood, 2012;Hatcher, 1994;Hintikka et al, 1998;Roberts et al, 1999;2000). The relationship with depression has been studied most frequently and relationships appear to be strong and robust when assessed using standardised measures and controlling for possible confounds (Besler & Stallones, 2008;Kaji et al, 2010; DEBT AND HEALTH Meltzer et al, 2010;2013;Pothen et al, 2003;Stuhldreher et al, 2007).. There is also limited evidence for a relationship with problems such as anxiety (Drentea, 2000;Drentea & Reynolds, 2012;Meltzer et al, 2013) and psychosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies did not find significant association (Hunt and Penland, 1999;Baune et al, 2006), and two other studies concluded that depression is associated with decreased levels of serum ferritin concentrations (Vahdat Shariatpanaahi et al, 2007;Baune et al, 2010). To date, no study has been conducted in Japan where the prevalence of depressive symptoms in general population is relatively high (Kaji et al, 2010). To address the gap in the literature, we conducted this study to examine the association between serum ferritin and depressive symptoms among Japanese municipal employees.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have investigated the types of adversity experienced in older adult life, which include personal illness, loneliness, bereavement (Hardy, Concato, & Gill, 2002;Prince, Harwood, Blizard, Thomas, & Mann, 1997), diminished social relationships, (Kaji, Mishima, Kitamura et al, 2010), forced change of residence, major negative revelations, marital difficulties (Murphy, 1982), divorce of children (Grimby & Svanborg, 1996) and loss of mobility and leisure activities (Hermans & Evenhuis, 2012). Research also suggests that expected events -transitions around the age of retirement, are associated with mental health decline (Carmichael, Hulme, & Porcellato, 2013).…”
Section: Introductionmentioning
confidence: 99%